Jembatan Komunikasi Visual Publik Melalui Running Text di Balai Desa Segodorejo - Septi Ambar Indraningtia Sukma; Azhar Irfana Gangsar; Anggi Indah Yuliana; Leni Dwi Apriliya; Achmad Naufal Amirul Hidayat; Moh Mansyur; Ahmad Nahrowi (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2025)
The rapid development of information technology has encouraged local governments, including village administrations, to adopt digital media for improving public communication. Segodorejo Village faced challenges in disseminating information, such as limited media access, low transparency, and ineffective public meetings. To address these issues, a community service program was implemented by installing a running text display at the Segodorejo Village Hall. The method included planning, installation, training, and evaluation involving village officials as direct beneficiaries. The results showed that the running text facilitated real-time information delivery, enhanced transparency, improved meeting effectiveness, and increased the digital capacity of village officials. Additionally, a manual book was provided as a practical guide to ensure sustainability. This initiative successfully contributed to strengthening the digital transformation of village governance toward a smart village concept.